Relationship between asthma control, health-related quality of life and subjective well-being in Czech adults with asthma - Elena Gurková; Patrice Popelková; Petr Otipka (University of Ostrava, 2015)
Aims: To investigate the relationship between asthma control, health related quality of life and subjective well-being in Czech adult patients with asthma. Design: A prospective observational cohort study. Methods: The sample included 316 people with asthma. In this 12-month observational study, patients were tested three times - at the baseline and after six and 12 months. Asthma control, health related quality of life and subjective well-being were assessed at the initial time point and followed up at six and 12 months by using the Asthma Control Test, the Mini Asthma Quality of Life Questionnaire and the Personal Well-being Index. Results: Level of asthma control and health related quality of life improved during the 12-month period, although spirometric parameters and subjective well-being were without significant change. Asthma control remained a significant predictor of health-related quality of life and general subjective well-being in linear regression models. Conclusions: Health-related quality of life is a construct based on a larger set of clinical variables when compared to subjective well-being. The regular monitoring of asthma control is associated with increased awareness and therapeutic expectations in patients, and better asthma control and health-related quality of life.